INCREASING RESILIENCE IN THE UNITED KINGDOM WAREHOUSE SECTOR IN RESPONSE TO SEVERE FIRE INCIDENTS - Fogarty, Anthony (Digital Repository of Theses, 2023)
This research set out to identify critical gaps in the overall business resilience of the warehouse sector in the context of fire safety. This need arose due to the increase in automation and an ever-increasing demand for warehouse space in the UK following COVID-19 and BREXIT, meaning warehouses were working at a greater capacity. Along with the literature review, a mixed methods approach was used for this study, incorporating qualitative and quantitative methods for collecting and analysing the data via interviews and a survey. Results showed that, while respondents were aware of trends that have impacted the warehouse sector, they were not aware of the increased fire risk, and what this may mean for overall business resilience. Furthermore, respondents showed gaps in their understanding regarding current fire safety regulations, insurance coverage and their responsibilities to the local community and environment in the event of a severe fire. They were further often unaware of the safety mechanisms in place within their own warehouses. Failure to adequately address these gaps could have severe financial, moral, and environmental implications for the business, potentially impacting its reputation in the local and broader business communities, and even resulting in business closure. This research recommends greater awareness regarding the impact of fires is necessary, and supports the need for better regulations along with support for measures such as sprinkler installation, especially for smaller warehouses. This research indicates that businesses operating from smaller warehouses are more likely to be exposed to higher risk factors. To validate and quantify this risk, further research into patterns of fires and business failure is necessary